Real-Life Radioactive Men: The Advantages and Disadvantages of Radiation Exposure - O'Doherty, Jim; Rojas-Fisher, Bruno; O'Doherty, Sophie (Superhero Science and Technology, 2018)
A common perception in modern society is that exposure to any amount of radiation is a bad thing and should be avoided at all costs. In the fictional superhero genre, exposure to radiation has been used as a vehicle to enable superpowers in what were previously ordinary humans. For instance, Dr Chen Lu, a Nuclear Physicist otherwise known as Radioactive Man, exposed himself to increasing amounts of radiation until he could endure a massive barrage, and in the process turned himself into Radioactive Man. In a similar fashion, Bruce Banner was exposed to a large amount of gamma radiation, giving him the superpowers of the Incredible Hulk. Although there is an element of truth in that the body can withstand low levels of radiation without any observable effects, there are many harmful side effects of being exposed to high levels of radiation. These harmful side effects form the underlying fear of the general publics’ understanding of radiation exposure. This article will explore in detail the reasoning behind the principles of radiation safety, and how different types of damage are caused to the human body when exposed to radiation. Furthermore, we discuss how cellular mutations are caused, as well as the potential of organisms to develop resistance to the harmful effects of radiation and the beneficial uses of radiation in the medical field for diagnosis and cancer treatment.